PENGARUH WOOD VINEGAR TERHADAP PERTUMBUHAN DAN PRODUKSI JAHE (Zingiber officinale Rosc.) - Nurliani Bermawie; Tjutju Nurhayati (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
The research to understand the effect of wood vinegar on the growth and yield of ginger was undertaken from November 2002 to March 2003 in Sukamulya Experimental Garden, Sukabumi. One high yielding and good quality ginger line (JPB4) were cut into small pieces about 50 g, and submerged in bactericide or wood vinegar solution 25 treatments were used, consists of control, bacteriside, Atonik, Gandasil and 3 types of wood vinegar (Pine, Mangrove and Acacia) at concentration 1,3 and 5% (v/v) combined with or without 200 g charcoal (Pine and Acacia). The research was designed in a randomized block with two replications. Observations were made on 58 growth percentage, disease incidence, growing components, yield and its components four months after planting. The results showed that the highest growth percentage were obtained from treatment with pine 1% and mangrove 3% combined with acacia charcoal and these were significantly different from control and bactericide treatment. Pine 1%, mangrove 3% with or without charcoal and acacia 5% added with acacia charcoal gave the highest value for growing components. For yield and its components, treatment with mangrove 1%, gave the longest rhizome 21,0 cm, while the widest of rhizome (7,3 cm) was obtained from pine 3% and biggest rhizome diameter was obtained from 5% (5,67 cm). Application of wood vinegar mangrove 1%, pine 1% also gave the highest rhizome weight (275,8 g/plant) and (265 g/plant) significantly different from control and bactericide application. On the whole pine 1%, mangrove 3% and acacia 5% were the best treatments for promoting ginger growth, while for effective control of bacterial wilt, higher concentration (5%) were needed.